Different propagules and auxin concentration on rooting of passionflower sandbank - Alexandre, Rodrigo Sobreira; Costa, Poliana Rangel; Chagas, Kristhiano; Mayrinck, Livia Giro; Giles, João Antônio Dutra; Schmildt, Edilson Romais (Revista Ceres, 2016)
Passiflora mucronata Lam. is resistant to Fusarim oxysporum f. passifloraceae and therefore can be used as rootstock for the species Passiflora edulis Sims. f. flavicarpa. The rootstocks in this case can be vegetatively propagated through cuttings. The objective of this study was to evaluate the effect of different types of cuttings and different concentrations of indole-3-butyric acid (IBA) on the adventitious rooting of P. mucronata. The experiments were arranged in a completely randomized design with four replications of 16 cuttings each. In Experiment 1, the treatments consisted of the different types of cuttings from mother plants grown in protected environment: shoot tips; two leaves and two nodes; one leaf and one node; leafless with two nodes; leafless with one node. In Experiment 2, the cuttings were taken from field plants and treated with the following IBA concentrations: 0; 1000 mg kg-1 (0.0036456 mol L-1); 1500 mg kg-1 (0.0054684 mol L-1) and 2000 mg kg-1 (0.0072912 mol L-1). The characteristics evaluated in the experiments 1 and 2 were: survival (1 and 2); budding (1 and 2); shoot number (2), shoot length (2), number of shoot leaves (2);shoot dry mass (2); callusing (1); rooting (1 and 2); root number (1 and 2), largest root length (1 and 2), root volume (1 and 2), and root dry mass (1 and 2). We found that, instead the shoot tips, the cuttings of the type leafless with two nodes are the best for P. mucronata rooting. Neither the cuttings from greenhouse plants nor the cuttings from field plants require growth regulators for rooting of P. mucronata cuttings of the type leafless with two nodes.

A espécie Passiflora mucronata Lam. é identificada como resistente ao Fusarim oxysporum f. passifloraceae e, portanto, pode ser utilizada como porta-enxerto para a espécie Passiflora edulis Sims. f. flavicarpa Deg., e a obtenção desses porta-enxertos pode dar-se por propagação vegetativa por estaquia. Objetivou-se, com este trabalho, avaliar diferentes tipos de estacas e diferentes concentrações do ácido indol-3-butírico (AIB), no enraizamento adventício de P. mucronata. Os experimentos foram realizados em delineamento inteiramente casualizado, com quatro repetições, de 16 estacas cada. No primeiro experimento, os tratamentos foram os diferentes tipos de estacas de plantas-matrizes de ambiente protegido: apical; de duas folhas e dois nós; de uma folha e um nó; sem folhas e dois nós; sem folhas e um nó. No segundo experimento, as estacas foram retiradas de campo e os tratamentos foram as concentrações de AIB: 0; 1000 (0,0036456 mol L-1); 1500 (0,0054684 mol L-1) e 2000 mg kg-1 (0,0072912 mol L-1). As características avaliadas no primeiro (1º) e no segundo (2º) experimentos foram: sobrevivência (1º e 2º); brotação (1º e 2º); número (2º), comprimento (2º), número de folhas (2º) e massa seca do broto (2º); calejamento (1º); enraizamento (1º e 2º); número (1º e 2º), comprimento (1º e 2º), volume (1º e 2º) e massa seca de raiz (1º e 2º). Recomenda-se usar estacas sem folhas e com dois nós, e não as apicais, para o processo de enraizamento de P. mucronata. O enraizamento das estacas sem folhas e com dois nós de P. mucronata dispensa o uso de reguladores de crescimento, tanto para as estacas provenientes de casa de vegetação quanto para as de campo.
Keywords: Passiflora mucronata Lam.; Vegetative propagation; Cutting; Auxin